Making Supplementary Foods Based on The Local Food of The Alor Community for Stunting Prevention (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
ABSTRACTThe case of stunting under five in North Mataru in 2019 was still very high at 51.8%. This percentage exceeds the national stunting percentage in 2019 which shows a declining trend of 27.67% (Rikesda 2018). Based on the results of the survey in the field, it is known that the local community has a variety of field products as local food. Local food produced is very diverse including rice, corn, tubers, and vegetables. This local food has sufficient nutritional value to meet the nutritional needs of toddlers in supporting toddler growth. The purpose of implementing this PKM is to provide understanding to the cadres of integrated service posts in North Mataru Village through the socialization of local food ingredients (brown rice and moringa) and the benefits of local food to prevent stunting and provide training on making local MP-ASI from brown rice ingredients and moringa. The results of this service activity showed that the participants became more aware of the benefits of local food to be processed into complementary foods (MP-ASI) in supporting toddler nutrition. In addition, the direct training made the participants more enthusiastic and gave a good assessment that they had gained new knowledge and skills. Participants who attended were also committed to continuing the results of the training to be passed on to other breastfeeding mothers.